Dually‐Passivated Perovskite Solar Cells with Reduced Voltage Loss and Increased Super Oxide Resistance. (4th March 2021) - Zhou, Qin; Gao, Yifeng; Cai, Chunsheng; Zhang, Zhuangzhuang; Xu, Jianbin; Yuan, Zhongyi; Gao, Peng
Abstract: In recent years, the power conversion efficiency (PCE) of perovskite solar cells (PSCs) has witnessed rapid progress. Nevertheless, the pervasive defects prone to non‐radiative recombination and decomposition exist at the surface and the grain boundaries (GBs) of the polycrystalline perovskite films. Herein, we report a comprehensive dual‐passivation (DP) strategy to effectively passivate the defects at both surface and GBs to enhance device performance and stability further. Firstly, a fluorinated perylene‐tetracarboxylic diimide derivative is permeated in the perovskite metaphase during antisolvent treatment, and then a fluorinated bulky aromatic ammonium salt is introduced over the annealed perovskite. The reduction of defect density can be unambiguously proved by the superoxide species generation/quenching reaction. As a result, optimized planar PSCs demonstrate a decreased open‐circuit voltages deficit from 0.47 to 0.39 V and the best efficiency of 23.80 % from photocurrent scanning with a stabilized maximum power output efficiency of 22.99 %. Without encapsulation, one typical device can maintain over 85 % of the initial efficiency after heating on a hot plate at 100 °C for 30 h under relative humidity (RH) of 70 %. When the device is aged under 30±5 % RH, over 97 % of its initial PCE is retained after 1700 h. Abstract : A practical and straightforward method to reduce the defects of polycrystalline perovskite films is exploited by introducing functional fluorinated molecules at two different stages of film formation. The PSCs based on the DP strategy can simultaneously improve device performance and stability by effectively inhibiting the formation of superoxide species due to minimized defects at the perovskite surface and GBs.